Policy Networks in Millennial Housing Development Through Social Media Marketing - Rizky Ilhami; Muhammad Fazri Candra; Soma Gantika (Journal of Research and Development on Public Policy, 2024)
The housing development policy network is a system or framework used by the government or related organizations to plan, coordinate, and implement various policies related to housing development. The main objective of the housing development policy network is to create decent, affordable, and sustainable settlements for the population. According to the Ministry of Public Works and Public Housing (PUPR), there are 81 million millennial Indonesians who do not yet own a house. To overcome this problem, strong collaboration between the government and related stakeholders is needed in creating new residential locations. Not only that, marketing millennial housing requires a marketing strategy that is close to young people, namely through social media. Thus, it is hoped that it will open up greater opportunities for the millennial age group to have housing.